The Effect of Financial Distress, Audit Opinion, and KAP Reputation on Auditor Switching - Abrianto, Kurnia Putra; Afandi, Agus (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This research aims to determine the influence of financial distress, audit opinion, and KAP reputation on auditor switching. This research uses a sample of infrastructure sector companies for the 2018-2022 periods. The number of companies used as a sample for this research is 34 companies with observations for 5 years. The method used in selecting samples was purposive sampling, the total sample for this research was 170 annual reports. The data collection method used is secondary data, namely data obtained by researchers indirectly through intermediary media and literature study. This research data was obtained from the official website of the Indonesian Stock Exchange, namely www.idx.co.id and several company websites. The results of this research show that KAP reputation has a negative and significant effect on auditor switching, while financial distress and audit opinion do not have a significant effect on auditor switching. Simultaneously and together, financial distress, audit opinion and KAP reputation have effect on Auditor Switching.